An investigation of conventional microbial culture for the Naja atra bite wound, and the comparison between culture-based 16S Sanger sequencing and 16S metagenomics of the snake oropharyngeal bacterial microbiota. - Yan-Chiao Mao; Han-Ni Chuang; Chien-Hung Shih; Han-Hsueh Hsieh; Yu-Han Jiang; Liao-Chun Chiang; Wen-Loung Lin; Tzu-Hung Hsiao; Po-Yu Liu (Public Library of Science (PLoS), 2021)
Naja atra is a major venomous snake found in Taiwan. The bite of this snake causes extensive wound necrosis or necrotizing soft tissue infection. Conventional microbial culture-based techniques may fail to identify potential human pathogens and render antibiotics ineffective in the management of wound infection. Therefore, we evaluated 16S Sanger sequencing and next-generation sequencing (NGS) to identify bacterial species in the oropharynx of N. atra. Using conventional microbial culture methods and the VITEK 2 system, we isolated nine species from snakebite wounds. On the basis of the 16S Sanger sequencing of bacterial clones from agar plates, we identified 18 bacterial species in the oropharynx of N. atra, including Morganella morganii, Proteus vulgaris, and Proteus mirabilis, which were also present in the infected bite wound. Using NGS of 16S metagenomics, we uncovered more than 286 bacterial species in the oropharynx of N. atra. In addition, the bacterial species identified using 16S Sanger sequencing accounted for only 2% of those identified through NGS of 16S metagenomics. The bacterial microbiota of the oropharynx of N. atra were modeled better using NGS of 16S metagenomics compared to microbial culture-based techniques. Stenotrophomonas maltophilia, Acinetobacter baumannii, and Proteus penneri were also identified in the NGS of 16S metagenomics. Understanding the bacterial microbiota that are native to the oropharynx of N. atra, in addition to the bite wound, may have additional therapeutic implications regarding empiric antibiotic selection for managing N. atra bites.